Strategies of attack and defence in woody plant–Phytophthora interactions - Oßwald, W; Fleischmann, F; Rigling, D; Coelho, A C; Cravador, A; Diez, J; Dalio, R J; Horta Jung, M; Pfanz, H; Robin, C; Sipos, G; Solla, A; et al. (Forest Pathology, 2014)
This review comprises both well-known and recently described Phytophthora species and concentrates on Phytophthora–woody plant interactions. First, comprehensive data on infection strategies are presented which were the basis for three models that explain invasion and spread of Phytophthora pathogens in different woody host plants. The first model describes infection of roots, the second concentrates on invasion of the trunk, and the last one summarizes infection and invasion of host plants via leaves. On the basis of morphological, physiological, biochemical and molecular data, scenarios are suggested which explain the sequences of reactions that occur in susceptible and tolerant plants following infections of roots or of stem bark. Particular emphasis is paid to the significance of Phytophthora elicitins for such host–pathogen interactions. The overall goal is to shed light on the sequences of pathogenesis to better understand how Phytophthora pathogens harm their host plants.
APS
Keywords: infection strategies; pathogens; Phytophora

Involvement of a cinnamyl alcohol dehydrogenase of Quercus suber in the defence response to infection by Phytophthora cinnamomi - Coelho, A C; Horta, M; Neves, D; Cravador, A (Physiological and Molecular Plant Pathology, 2006)
A gene encoding a potential NADPH-dependent cinnamyl alcohol dehydrogenase (QsCAD1) (GenBank accession no: AY362455) was identiﬁed in Quercus suber (cork oak). Its complete cDNA sequence was obtained by RACE-PCR, starting from total RNA extracted from roots of seedlings of Q. suber, infected with Phytophthora cinnamomi, the causal agent of the decline and sudden death of Q. suber and Quercus ilex subsp. rotundifolia in the Iberian Peninsula. Sequence information to perform the RACE-PCR was acquired from a polymorphic fragment (C9), speciﬁcally identiﬁed by cDNA-AFLP, in leaves of epicormic shoots of a cork oak tree that suffered sudden death. RT-PCR and hybridization analysis showed that the QsCAD1 gene is up-regulated in root seedlings of Q. suber infected with P. cinnamomi. QsCAD1 has a high structural homology with VR-ERE (Vigna radiata), an enzyme that detoxiﬁes eutypine (produced by Eutypa lata, the causal agent of eutypa dieback of grapevines), to eutypinol, and with QrCAD1 (Q. ilex subsp. rotundifolia), EgCAD1 (Eucalyptus gunnii), MdCAD1 (Malus x domestica). Taken together, these results suggest that these enzymes, and namely QsCAD1 belong to a new group of CAD potentially involved in deactivation of toxins produced by phytopathogens.
Keywords: cinnamyl alcohol dehydrogenase; defence response; oak tree; phytophthora cinnamomi

Crystallization and preliminary x-ray diffraction analysis of beta-cinnamomin, an elicitin secreted by the phytopathogenic fungus Phytophthora cinnamomin. - Archer, M; RODRIGUES, M L; Aurélio, M; Biemans, R; Cravador, A; Carrondo, M a (Acta crystallographica. Section D, Biological crystallography, 2000)
Cinnamomin (CIN) belongs to a family of 10 kDa proteins designated as elicitins. Some of these proteins induce a hypersensitive response in diverse plant species, leading to resistance against fungal and bacterial plant pathogens. CIN was crystallized by the vapour-diffusion method using either ammonium sulfate or polyethyleneglycol (PEG) as precipitants in solutions buffered at around pH 7. These crystals are isomorphous and belong to the triclinic space group, with unit-cell parameters a = 31.69, b = 36. 99, c = 44.09 A, alpha = 76.86, beta = 84.41, gamma = 80.26 degrees. A frozen crystal diffracted X-rays beyond 1.45 A resolution on a synchrotron-radiation source.
Keywords: Beta-cinnamomin; Elicitins; Phytopathogenic fungi

Highly specific and sensitive non-radioactive molecular identification of Phytophthora cinnamomi - Coelho, A C; Cravador, A; Bollen, A (Mycological Research, 1997)
In response to the need for a faster, more reliable method for identifying Phytophthora cinnamomi in cork oak soils in Portugal, a simple, fast, sensitive molecular identi®cation method is described. It is based on a colorimetric assay which involves an oligonucleotide capture probe covalently immobilised on microtitration wells, a multi-biotinylated oligonucleotide detection probe and the PCR-ampli®ed target DNA. The target DNA is a 349 bp DNA fragment partially covering the 3«-translated and 3«- untranslated regions of the cinnamomin gene. When the speci®city of the PCR reaction was evaluated in vitro using isolates of P. cinnamomi and eight other Phytophthora species, including the related P. cambivora, it was speci®c to P. cinnamomi. When 30 isolates of P. cinnamomi from oak roots in southern Portugal were assayed, 26 gave a strong positive response. The assay has a sensitivity of about 2±5 genome equivalents of P. cinnamomi. The reason for the negative response of four isolates remains unclear.
Keywords: Cork oak soils; Iidentification method; phytophthora cinnamomi